Lacunae Infills for in Situ Treatment of Historic Glazed Tiles - Mendes, Marta T. (2017)
Knowledge of current conservation materials and methods together with those adopted in the past is essential to aid research and improve or develop better conservation options. The infill and painting of tile lacunae are subjected to special requirements mainly when used in outdoor settings. A selection of the most commonly used materials was undertaken and performed based on inquiries to practitioners working in the field. The infill pastes comprised organic (epoxy, polyester), inorganic (slaked lime,hydraulic lime and zinc hydroxychloride) and mixed organic–inorganic (slaked lime mixed with a vinylic resin)binders. The selected aggregates were those most commonly used or those already present in the commercially formulated products. The infill pastes were characterised by SEM, MIP, open porosity, water absorption by capillarity, water vapour permeability, thermal and hydric expansibilities and adhesion to the ceramic body. Their performance was assessed after curing, artificial ageing (salt ageing and UV–Temp–RH cycles) and natural ageing. The results were interpreted in terms of their significance as indicators of effectiveness, compatibility and durability